To simplify the expression \(-5\sqrt{6} - 7\sqrt{150}\), we first need to simplify \(\sqrt{150}\).
-
Simplifying \(\sqrt{150}\): \[ \sqrt{150} = \sqrt{25 \times 6} = \sqrt{25} \times \sqrt{6} = 5\sqrt{6} \]
-
Substituting back into the expression: \[ -5\sqrt{6} - 7\sqrt{150} = -5\sqrt{6} - 7(5\sqrt{6}) = -5\sqrt{6} - 35\sqrt{6} \]
-
Combining like terms: \[ -5\sqrt{6} - 35\sqrt{6} = (-5 - 35)\sqrt{6} = -40\sqrt{6} \]
Thus, the expression \(-5\sqrt{6} - 7\sqrt{150}\) simplifies to \(-40\sqrt{6}\).
The final answer is: \[ \boxed{-40\sqrt{6}} \]